Common Fisheries Policy of the EU through the Lens of Multi-Level Governance Framework - V. O. Kolomin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The fishery sector has a unique position within the European Union regulatory system. Being in the joint competence of supranational and national authorities, it has a complex transnational nature, characterized by an active participation of non-governmental organizations and associations, as well as a number of coordinating international authorities. Additionally, the fishery is of particular importance for nation states since it is linked to issues of sovereignty and social stability. The paper examines possible applications of the multi-level governance (MLG) theory to the study of the EU’s Common Fisheries Policy (CFP), its history, current state and prospects for development. The first section outlines the key provisions of the MLG theory and describes its general applicability to the study of the EU institutions. In order to provide a better understanding of strengths and weaknesses of the MLG theory, the author compares it to a number of related approaches traditionally used in integration studies in general and the European integration studies in particular. The author concludes that the multi-level governance framework is particularly suitable to the study of complex regulatory processes that involve different actors, like in the case of the EU CFP. Such an approach allows the author to identify certain specifics of the EU political practices in this area of regulation. For example, the author highlights a clear desire of the supranational bodies to acquire additional competences and to bring about redistribution of power in their favor through mobilizing the support of sub-national actors and think-tanks and at the expense of national actors. However, the author concludes that in order to provide a truly comprehensive understanding of the EU CFP, the traditional focus of the MLG approach should be expanded to encompass yet another level of analysis — the global one.